Influence of cation vacancy related defects on the self-assembly processes in CdSe/ZnSe quantum dot heterostructures - Borkovska, L.V.; Korsunska, N.O.; Kushnirenko, V.I.; Sadofyev, Yu.G.; Sheinkman, M.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A spatial distribution of the cation vacancy related defects and their influence on the formation processes of self-assembled nanoislands in CdSe/ZnSe heterostructures were investigated by photoluminescence methods. Self-assembling growth was achieved under low temperature (2300C) molecular beam epitaxy with a subsequent annealing step. To change a number of cation vacancy related defects a VI/II beam pressure ratio РVI/РII was varied from 2:1 to 5:1. In the samples grown under РVI/РII = 5:1 a significant increase of self activated emission band caused by cation vacancy related defects was found. A study of the excitation spectra of defect related band revealed that in all samples the cation vacancy related defects are present in ZnCdSe wetting layer. In the samples grown under РVI/РII = 5:1 they were observed on nanoisland interface too. It was found that the increase of Se beam pressure results also in high energy shift and narrowing of nanoisland emission band. This process is accompanied by low energy shift of ZnSe band-to-band emission. Observed changes in photoluminescence spectra are explained by the decrease of Cd content in ZnCdSe layer due to enhancement of Cd/Zn interdiffusion process in the result of the increase of vacancy related defect number.